Peluang Pendidikan Islam di Era Globalisasi : Menuai Tantangan, Meraih Peluang - Nur Selawati (CV. Syntax Corporation Indonesia, 2022)
Along with the times, the competition for life in various aspects is also getting tighter, the challenges faced are also very diverse, as is what happened in the world of education, especially in Islamic education, but various challenges must be anticipated so that education can be implemented and implemented according to its mission and objectives . If a challenge can be anticipated and faced properly, it often becomes a very efficient opportunity, on the contrary if it is not able to be faced properly, it often becomes an obstacle that greatly interferes with efforts to implement and implement the mission and goals of Islamic education. Therefore, reformatting educational theory and practice must be carried out and balanced immediately, so that Islamic education will not only reap challenges, but also seize opportunities. The method used in this research is library research. library research is also a part of qualitative research methods with secondary data sources, namely books and journals related to Islamic education opportunities. In the research conducted, it has been concluded that one of the challenges faced by Islamic education is by taking advantage of global opportunities, advances in information, communication and science and technology to strengthen the position of Islamic education. However, Islamic education is required to maintain a selective, critical, and open attitude towards the emergence of globalization so that the opportunities for Islamic education are always superior and taken into account.